Image-guided radiotherapy for prostate cancer with cone beam CT: dosimetric effects of imaging frequency and PTV margin. Issue 1 (October 2016) - Ariyaratne, Hemal; Chesham, Hayley; Pettingell, John; Alonzi, Roberto
Abstract: Background and purpose: This study assesses the effect of frequency of cone beam CT (CBCT) verification imaging on dose–volume parameters during image-guided radiotherapy (IGRT) for prostate cancer. It also investigates the dosimetric impact of reducing the planning target volume (PTV) margin, when daily imaging is used. Material and methods: 844 CBCT images from 20 patients undergoing radical prostate radiotherapy were included. Patients received a dose of 74 Gy in 37 fractions using 7-field intensity-modulated radiotherapy (IMRT). Clinical target volume (CTV) and organs at risk were contoured manually on each slice of every CBCT image. A daily online CBCT verification schedule was compared with a protocol of verification on days 1–3 followed by weekly online imaging. PTV margins of 3 mm, 5 mm, and 7 mm were compared for the daily imaging protocol. Results: 90% of patients had improved target coverage with daily online in comparison to weekly online imaging. A median of 37 fractions per treatment course achieved CTV coverage with daily imaging compared to 34 fractions with a weekly online protocol. 80% of patients had a reduction in rectal dose with the daily protocol. PTV margin reduction to 5 mm with adequate target coverage was feasible with daily imaging. Conclusions: Daily online CBCT verification improves CTV coverage and reduces rectal dose during IGRT for prostate cancer. Tighter PTV margins could be considered with daily CBCT use.